Examining Eating Out Patterns among Individuals in Kumasi Metropolis, Ghana - Prempeh Duah, Kelvin; Oscar Agyemang Opoku (The Indonesian Institute of Science and Technology Research, 2025)
Eating out refers to consuming meals at food service establishments. Over the past decade, individuals’ eating out behavior has changed significantly. This study examined eating out patterns in Kumasi Metropolis. Guided by a positivist paradigm, a cross-sectional quantitative survey was conducted with 400 respondents. Data were analyzed using descriptive statistics and chi-square tests with SPSS. The study found that eating out was common at various urban food premises. Most respondents ate out on weekdays, with fewer doing so on weekends. Lunch was the most frequently consumed meal, and local dishes were preferred over continental cuisine. Gender, age, marital status, and education were significantly related to eating out patterns. Younger respondents favored fast food and continental meals, while older individuals preferred restaurants and chop bars serving local foods. It is recommended that food vendors target younger individuals and females with promotions and convenient meal options. Chop bars and restaurants should improve offerings and marketing to attract older and male customers. Dining establishments should also adapt menus to suit different socio-demographic preferences, such as providing both local and continental dishes to broaden their appeal.